MANAJEMEN PRODUKSI PROGRAM “MOJOK MENTOK” MEDIA ONLINE MOJOK.CO PADA TAHUN 2022/2023 - Zakiy Fatih, Muhammad Ghulam; Winata, Muhammad Danu (Universitas Negeri Surabaya, 2024)
Research on program production management is an interesting research. In this study, researchers chose the